Tactile-Sight: A Sensory Substitution Device Based on Distance-Related Vibrotactile Flow. (17th June 2013) - Cancar, Leandro; Díaz, Alex; Barrientos, Antonio; Travieso, David; Jacobs, David M.
Sensory substitution is a research field of increasing interest with regard to technical, applied and theoretical issues. Among the latter, it is of central interest to understand the form in which humans perceive the environment. Ecological psychology, among other approaches, proposes that we can detect higher-order informational variables (in the sense that they are defined over substantial spatial and temporal intervals) that specify our interaction with the environment. When using a vibrotactile sensory substitution device, it is reasonable to ask if stimulation on the skin may be exploitable to detect higher-order variables. Motivated by this question, a portable vibrotactile sensory substitution device was built, using distance-based information as a source and driving a large number of vibrotactile actuators (72 in the reported version, 120 max). The portable device was designed to explore real environments, allowing natural unrestricted movement for the user while providing contingent real-time vibrotactile information. Two preliminary experiments were performed. In the first one, participants were asked to detect the time to contact of an approaching ball in a simulated (desktop) environment. Reasonable performance was observed in all experimental conditions, including the one with only tactile stimulation. In the second experiment, a portable version of the device was used in a real environment, where participants were asked to hit an approaching ball. Participants were able to coordinate their arm movements with vibrotactile stimulation in appropriate timing. We conclude that vibrotactile flow can be generated by distance-based activation of the actuators and that this stimulation on the skin allows users to perceive time-to-contact related environmental properties.